Antiviral drug resistance rates among patients with chronic hepatitis B infection - Özlük, Suat; Bayram, Yasemin; Özkaçmaz, Ayşe; Parlak, Mehmet; Özdemir, Ayşe; Aypak, Cenk (European Journal of Clinical and Experimental Medicine, 2023)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Chronic hepatitis B infection (CHB) affects millions of people around the world. Many clinicians find it challenging to choose therapeutic agents due to the mutations that occur in the hepatitis B virus (HBV) that cause drug resistance. Thus, the aim of this study was to determine the HBV resistance rates against the currently recommended first-line therapies in the region of our country where HBV prevalence is high. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A total of 96 patients (56 men and 40 women) with HBV infection were enrolled in the study. The serum samples collected from those were analyzed with real-time polymerase chain reaction analysis followed by pyrosequencing (PyroStar HBV Drug Resistance Test, Altona Diagnostics, Germany) for drug resistance mutations associated with lamivudine, adefovir, telbivudine, entecavir, and tenofovir. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. HBV drug-resistance mutations were investigated in 80 treatment-naïve and 16 treatment-experienced patients (6 entecavir, 4 PEGylated-interferon, 4 tenofovir, 2 lamivudine). None of the HBV-DNA samples had mutations cause to drug resistance were detected in any codons regions that were analyzed. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Antiviral resistance poses serious obstacles for clinicians in the treatment of CHB. Determining whether antiviral resistance exists in HBV is critical to choose the appropriate treatment agent.